2018
DOI: 10.1017/s0007114518003112
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of vitamin A status among pregnant women in Western Brazilian Amazon

Abstract: Determining the predictors of serum retinol at mid-pregnancy is relevant for planning interventions aimed at improving vitamin A status of pregnant women and their offspring. This prospective study assessed predictors of serum retinol at the beginning of the third trimester of pregnancy. We enrolled 442 pregnant women living in the urban area of Cruzeiro do Sul, Western Brazilian Amazon. Demographic, socio-economic, environmental and clinical characteristics as well as obstetric history, anthropometric, dietar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
1
5
0
2
Order By: Relevance
“…In our study, the median plasma retinol for women in mid-pregnancy (1.26 µmol/L) and late pregnancy (1.07 µmol/L) was similar to those from a Beijing study (1.29 and 1.15 µmol/L) [24], but lower than those from a Chinese national survey (1.64 and 1.52 µmol/L) [10], likely due to differences in population characteristics related to the sample selections. Two international studies reported retinol concentration by trimester of pregnancy [14,25], 1.90 µmol/L for Brazilian women during mid-pregnancy [14] and 1.33 µmol/L for English women during late pregnancy [25]. Our study showed that the prevalence of vitamin A deficiency was 2.6% for pregnant women.…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…In our study, the median plasma retinol for women in mid-pregnancy (1.26 µmol/L) and late pregnancy (1.07 µmol/L) was similar to those from a Beijing study (1.29 and 1.15 µmol/L) [24], but lower than those from a Chinese national survey (1.64 and 1.52 µmol/L) [10], likely due to differences in population characteristics related to the sample selections. Two international studies reported retinol concentration by trimester of pregnancy [14,25], 1.90 µmol/L for Brazilian women during mid-pregnancy [14] and 1.33 µmol/L for English women during late pregnancy [25]. Our study showed that the prevalence of vitamin A deficiency was 2.6% for pregnant women.…”
Section: Discussionsupporting
confidence: 46%
“…Reports on vitamin A by trimester of pregnancy were limited [10,14,23,24]. In our study, the median plasma retinol for women in mid-pregnancy (1.26 µmol/L) and late pregnancy (1.07 µmol/L) was similar to those from a Beijing study (1.29 and 1.15 µmol/L) [24], but lower than those from a Chinese national survey (1.64 and 1.52 µmol/L) [10], likely due to differences in population characteristics related to the sample selections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, we have published few papers on baseline data 10 11 31–34. Key reports included poor serum retinol status observed throughout pregnancy31 found to be negatively associated with maternal haemoglobin (β −3.30 g/L; 95% CI −6.4 to –0.20) and newborn birth weight (β −0.10 kg; 95% CI −0.20 to –0.00) 11. According to WHO, 7.8% and 41.8% of all pregnancies worldwide are affected by gestational night blindness and anaemia, respectively 35 36.…”
Section: Findings To Datementioning
confidence: 99%
“…iii) fatores relacionados à mulher: situação conjugal (casada ou mora com companheiro), presença do pai da criança no domicílio; iv) obstétricos e de saúde: tipo de parto, número de gestações, paridade (número de gestações), anemia no parto, peso pré gestacional, ganho de peso na gestação, xeroftalmia na gestação avaliada por meio de entrevista padronizada proposta pela OMS e adaptada para o Brasil ( NEVES et al, 2019); v) fatores relacionados ao bebê: sexo, peso e comprimento ao nascer, apgar, idade gestacional de nascimento, se houve aleitamento materno na primeira hora de vida, tipo de aleitamento.…”
Section: Coleta De Dados Na Linha De Baseunclassified